2005
DOI: 10.1080/01650250444000315
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of delivery mode and other programme characteristics for the effectiveness of early childhood intervention

Abstract: Although it is generally believed that early intervention programmes are an effective means to stimulate children's cognitive development, many questions remain concerning programme design and delivery. This article reviews 19 studies into the effectiveness of early intervention programmes published from 1985 onward. The database comprised 85 different outcomes or effect sizes (71 in the cognitive domain, 14 in the socioemotional domain). The overall effect size estimate was d ¼ 0.32 (SE ¼ 0.05) in the cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 67 publications
4
90
2
10
Order By: Relevance
“…In fact, a meta-analysis of a variety of parent training programs designed to improve parental sensitivity and child attachment found that programs were more effective if they provided video feedback (feedback on videotaped parent-child interactions) (Bakermans-Kranenburg et al, 2003). A 2005 meta-analysis of home-and center-based programs by Blok, Fukkink, Gebhardt, and Leseman (2005) found that having some form of parent -coaching,‖ including modeling, was related to larger effects on cognitive measures. A more recent meta-analysis of programs that provided training in parenting skills also found larger impacts for programs that gave parents an opportunity to practice the skills taught (Kaminsky et al, 2008).…”
Section: Running Head: Added Impact Of Parenting Education In Preschomentioning
confidence: 99%
“…In fact, a meta-analysis of a variety of parent training programs designed to improve parental sensitivity and child attachment found that programs were more effective if they provided video feedback (feedback on videotaped parent-child interactions) (Bakermans-Kranenburg et al, 2003). A 2005 meta-analysis of home-and center-based programs by Blok, Fukkink, Gebhardt, and Leseman (2005) found that having some form of parent -coaching,‖ including modeling, was related to larger effects on cognitive measures. A more recent meta-analysis of programs that provided training in parenting skills also found larger impacts for programs that gave parents an opportunity to practice the skills taught (Kaminsky et al, 2008).…”
Section: Running Head: Added Impact Of Parenting Education In Preschomentioning
confidence: 99%
“…Daarnaast spelen de attitudes en percepties van ouders ten aanzien van maatschappij en onderwijs een rol. Uit onderzoek blijkt bijvoorbeeld dat het combineren van ontwikkelingsstimulering op school en in de thuissituatie bij jonge kinderen een positief effect heeft op hun cognitieve ontwikkeling (Blok et al, 2005). Tevens blijkt het bevorderlijk te zijn voor de leerprestaties en ontwikkeling van kinderen wanneer zij thuis worden ondersteund, gestimuleerd en gemotiveerd (zie ook Epstein, 2001;Oostdam & Hooge, 2012;Smit et al, 2007).…”
Section: Het Belang Van Gezinsstructuur En Gezinsopvoedingunclassified
“…Le programme a aussi été conçu selon les données probantes concernant l'efficacité des interventions en petite enfance. Ainsi, il favorise l'implication directe du parent et il inclut des activités en groupe et à la maison (Blok et al, 2005;Bronfenbrenner, 1979), il est offert 127 par des intervenants qualifiés (Anderson et al, 2003;Denis, Malcuit, & Pomerleau, 2005) et le choix des activités et leurs séquences ont été établis selon des inventaires de développement normalisés (Brigance, 1994(Brigance, , 1997.…”
Section: Instruments De Mesureunclassified
“…Dans une synthèse portant sur la lecture conjointe, Scarborough et Dobrich (1994) soulignent l'importance d'une attitude positive du parent face à la lecture. En ce sens, les auteurs s'accordent généralement pour encourager l'implication active des parents dans les programmes d'intervention (Blok, Fukkink, Gebhardt, & Leseman, 2005;Boyce, Cook, Roggman, Innocenti, Jump, & Akers, 2004;Eamon, 2000;Lahaie, 2008 1. l'utilisation de techniques évocatrices qui encouragent la participation active de l'enfant dans la narration de l'histoire; 2. la rétroaction sous forme d'encouragements, de commentaires et de corrections; 3. l'adaptation progressive de l'adulte pour demeurer au même niveau ou à un niveau légèrement supérieur aux habiletés de l'enfant (Arnold & Whitehurst, 1994).…”
unclassified